The International business environments of franchising in BRICS economies - SAYL, ZINEB (Archives of Business Research, 2022)
This article aims to analyze the factors that explain the growth and success of the franchising in BRICS economies, and study the long-term relationship between determinants and impacts of franchising in these economies. We propose a panel data regression model for determining the factors affecting the franchising market in BRICS economies. The model is designed for the time period of 2000-2019. We use a Granger causality to study the long-term relationship between determinants and impacts of franchising. The Results suggests that the development of franchising in BRICS economies is determinated by economic, social, political and legal factors. On the one hand GDP per capita and degree of International competitiveness has a positive impact on franchise, so the purchasing power and the level of individual income affect franchising investment. On the other hand, the market size and level of urbanization have an important impact on franchising investment. Although, there is evidence of interactions between determinants and impacts of franchising in BRICS economies.